An Annotated Bibliography on the Relationship between Technological Change and Educational Development - Whiston, Tom.; United Nations Educational, Scientific, and Cultural Organization, Paris (France). International Inst. for Educational Planning (Washington, D.C. : Distributed by ERIC Clearinghouse, 1980)
Comprising 387 citations, this annotated bibliography is concerned with both the implications of technological change for educational policy and the effects of education on technology. The editors' introduction gives a brief discussion of education and technology in developing and developed nations and notes that the bibliography covers only articles published in English (or in both English and French), primarily in the 1970s. The citations are presented under eight categories, including (1) the impact of technology on education and society; (2) social and educational constraints on technology; (3) technology's effects on manpower training and retraining; (4) technological change in specific industries and professions; (5) planning and development; (6) geographic, regional, and development issues; (7) educational technology, especially for the handicapped; and (8) publications by international organizations. Appended are an author index and a list of English organizations from which to get additional information. (Author/RW)
Availability: IIEP Publications, International Institute for Educational Planning, 7-9, rue Eugene-Delacroix, 75016 Paris, FRANCE (Order No. H.36; 30.00 francs). Also available in French edition.
Sponsoring Agency: Canadian International Development Agency, Ottawa (Ontario).
Sponsoring Agency: Norwegian Agency for Development Aid, Oslo.
Microfiche.
Keywords: Developed Nations; Reference Materials, Bibliographies; Books